Common mental health problems in rural-to-urban migrant workers in Shenzhen, China: prevalence and risk factors. (9th January 2017) - Zhong, B. L.; Liu, T. B.; Chan, S. S. M.; Jin, D.; Hu, C. Y.; Dai, J.; Chiu, H. F. K.
Abstract : Aims: Rural-to-urban migrant workers are a large marginalised population in urban China. Prevalence estimates of common mental health problems (CMHPs) in previous studies varied widely and very few studies have investigated migration-related factors of CMHPs in migrant workers. The objective of this study was to determine the prevalence and risk factors of CMHPs among Chinese migrant workers. Methods: A random sample of 3031 migrant workers of ten manufacturing factories in Shenzhen, China, completed a standardised questionnaire containing socio-demographic and migration-related variables and the Chinese 12-item General Health Questionnaire (GHQ-12). A GHQ-12 score of three or higher was used to denote the presence of CMHPs. Results: The prevalence of CMHPs was 34.4% in Chinese migrant workers. In multiple logistic regression, risk factors for CMHPs included being 16–25 years old (odd ratio [OR] 1.65, 95% confidence interval [CI] 1.28, 2.12), being 26–35 years old (OR 1.36, 95% CI: 1.05, 1.75), low monthly income (OR 1.42, 95% CI 1.04, 1.92), poor living condition (OR: 1.76, 95% CI: 1.22, 2.54), physical illness in the past 2 weeks (OR 1.72, 95% CI 1.43, 2.05), having worked in many cities (OR 1.34, 95% CI 1.03, 1.74), infrequently visiting hometown (OR 1.56, 95% CI 1.22, 1.99), poor Mandarin proficiency (OR 1.51, 95%CI 1.13, 2.01), a low level of perceived benefits of migration (OR 1.33, 95% CI 1.14, 1.55) and working more than 8 h/day (OR 1.39, 95% CI 1.14, 1.70). Conclusions: CMHPs are very prevalent among Chinese migrant workers. Given the large number of Chinese migrant workers, there is an urgent need to address the mental health burden of China's migrant worker population.